Plan de manejo ambiental pozos exploratorios Bloque Huila Norte estudiando implementar sus locaciones en madera (1998)
In the area of interest for the search and use of hydrocarbons belonging to the Huila Norte Block, the company SIPETROL S.A. has defined a zone for the development of exploratory drilling projects, which will allow it to evaluate potential reserves and, based on the results, establish actions for their future use. Within the legal framework and to achieve the optimal development of this project, the Environmental Evaluation and Management Document for the Drilling of Three Exploratory Wells in the Exploratory Drilling Area of the Huila Norte Block is presented, whose objective is to define the mechanisms aimed at making exploratory drilling activities compatible with the particularities of the environment.